2017
DOI: 10.3386/w23242
|View full text |Cite
|
Sign up to set email alerts
|

When Harry Fired Sally: The Double Standard in Punishing Misconduct

Abstract: We examine gender differences in misconduct punishment in the financial advisory industry. We find evidence of a "gender punishment gap": following an incident of misconduct, female advisers are 20% more likely to lose their jobs and 30% less likely to find new jobs relative to male advisers. Females face harsher outcomes despite engaging in misconduct that is 20% less costly and having a substantially lower propensity towards repeat offenses. The gender punishment gap in hiring and firing dissipates at firms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 36 publications
15
70
0
Order By: Relevance
“…Furthermore, it seems that pay disparity has been only one of several problems. Egan, Matvos, and Seru () found that firms had a disproportionate share of misconduct complaints against women initiated by their employers, as compared to male employees working in the financial advisory profession. They categorized the complaints of misconduct as related to fraud, fiduciary duty, negligence, risky investments, churning/excessive trading, omission of key facts, unsuitability, misrepresentation, unauthorized activity, fee/commission‐related, and other issues.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it seems that pay disparity has been only one of several problems. Egan, Matvos, and Seru () found that firms had a disproportionate share of misconduct complaints against women initiated by their employers, as compared to male employees working in the financial advisory profession. They categorized the complaints of misconduct as related to fraud, fiduciary duty, negligence, risky investments, churning/excessive trading, omission of key facts, unsuitability, misrepresentation, unauthorized activity, fee/commission‐related, and other issues.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…For men, 28% of the complaints were employer‐initiated, and 55% were consumer‐initiated. Egan et al also found that female employees in the financial advisory profession were 20% more likely, as compared to men, to lose their jobs, and 30% less likely to find a new job after being fired (Egan et al, ). Women were punished more harshly even though the gross misconduct by men was three times more likely to happen, twice as likely to repeat, and 20% higher in cost to the company (Egan et al, ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospido, Laeven, and Lamo (2019) show gender differences exist in career progression and promotions in central -6 -banking. Egan, Matvos, and Seru (2017) show female advisers face harsher outcomes following misconduct, but this effect is mitigated in firms with more female executives. Adams and Ragunathan (2017) show gender barriers tend to discourage women from working in finance.…”
Section: Introductionmentioning
confidence: 96%
“…This is suggestive of higher historical institutional supply-side hurdles and is supportive of a selection mechanism whereby only the most talented female artists enter the profession. Similar dynamics have also recently been observed in a study involving a field experiment on a large online Q&A forum (Bohren, Imas, & Rosenberg) as well as for the case of the referee process in academic journals (Hengel), patent applications (Jensen, Kovács, & Sorenson, 2018) as well as investment advice (Botelho & Abraham, 2017;Egan, Matvos, & Seru, 2017). Second, we show that women are less likely to be sold in the secondary (auction) market, where artists traded who have a resale value.…”
Section: Introductionsupporting
confidence: 85%